2002
DOI: 10.2337/diabetes.51.9.2734
|View full text |Cite
|
Sign up to set email alerts
|

Androgens Decrease Plasma Adiponectin, an Insulin-Sensitizing Adipocyte-Derived Protein

Abstract: Adiponectin, an adipose-specific secretory protein, exhibits antidiabetic and antiatherogenic properties. In the present study, we examined the effects of sex hormones on the regulation of adiponectin production. Plasma adiponectin concentrations were significantly lower in 442 men (age, 52.6 ؎ 11.9 years [mean ؎ SD]) than in 137 women (53.2 ؎ 12.0 years) but not different between pre-and postmenopausal women. In mice, ovariectomy did not alter plasma adiponectin levels. In contrast, high levels of plasma adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

56
513
19
23

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 728 publications
(611 citation statements)
references
References 48 publications
56
513
19
23
Order By: Relevance
“…In addition, in a multiple linear regression analysis that included body size and body fat distribution, sex again had an independent effect on adiponectin concentrations. This finding of a sex-based difference in plasma adiponectin concentra- tions is supported by some [28,31,55] but not all [30,56] other studies. However, the current findings are the first to account for the known sex-based differences in body fat distributions and strongly support the concept that sex has an additional independent effect to modulate adiponectin concentrations.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, in a multiple linear regression analysis that included body size and body fat distribution, sex again had an independent effect on adiponectin concentrations. This finding of a sex-based difference in plasma adiponectin concentra- tions is supported by some [28,31,55] but not all [30,56] other studies. However, the current findings are the first to account for the known sex-based differences in body fat distributions and strongly support the concept that sex has an additional independent effect to modulate adiponectin concentrations.…”
Section: Discussionmentioning
confidence: 58%
“…The number of fat cells and fat cell size, both of which vary between sexes, are possible determinants of adiponectin production rates. Furthermore, it was recently reported that androgens decrease plasma adiponectin concentrations in vivo as well as adiponectin secretion from 3T3-L1 adipocytes in vitro [55].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Androgens reduce plasma adiponectin, explaining the lower plasma protein levels observed among men, as well as some of the increased risk of insulin resistance and atherosclerosis in these individuals, compared with women [47]. Surprisingly, adiponectin levels were elevated among individuals with macroalbuminuria compared with those with normal albumin excretion.…”
Section: Discussionmentioning
confidence: 97%
“…Sexual dimorphism in terms of total systemic adiponectin, with women having higher levels of adiponectin than men, has been reported [10,42,43]. Although this was preserved in CSF [18], such findings were achieved using assay-based measures.…”
Section: Discussionmentioning
confidence: 99%